Company-Based Agreements Secure Employment - Hartmut Seifert; Toralf Pusch (Wirtschaftsdienst)
Abstract This article provides some empirical results on company-based agreements to safeguard employment during the pandemic from a representative survey of works councils. The agreed contents are compared with those of the financial crisis of 2009 in order to check whether certain basic patterns have changed due to experience-saturated practice, or if new specifics develop in the face of changed problem constellations. During the pandemic, as in the financial crisis, agreements on adjustments to working hours (internal flexibility) versus monetary ones dominate. Finally, it is discussed what conclusions to be drawn in the event of a possible renewed economic downturn.